Collector Efficiency of the Polymer Solar Collector - Mohd Rosli, Mohd Afzanizam; Mat, Sohif; Sharif, Mohd Khairul Anuar; Sopian, Kamaruzzaman; Sulaiman, M. Yusof; Salleh, Elias @ Ilias (American-Eurasian Network for Scientific Information, 2014)
This paper examines the collector efficiency (F’) of the polymer collector in variation of plate thickness, top heat loss coefficient and ratio of the thermal conductivity to plate thickness (H). The collector efficiency reduced with the increase of the thickness for all cases of top heat loss coefficient (Ut) as expected. Furthermore, the higher H value increased the F’ for all conditions of Ut. The suitable thickness of the collector has been determined in the range of 1.5 to 2.5 mm base on the F’. The top losses heat transfer coefficient should be minimize to obtain higher performance. The polymer collector needs to be optimum design to compensate the low thermal conductivity of the material.